ANALISIS KUALITAS LAYANAN INTERNET BANKING DENGAN MENGGUNAKAN METODE E-SERVQUAL PADA BANK XYZ - Heryanto, Nicolas; H. Sutawidjaya, Ahmad (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2017)
This research tries to analyze the quality of internet banking service of XYZ Bank with the aim to know attribute on internet banking service quality which need to be improved and maintained. The method used is E-SERVQUAL by using six dimensions of efficiency; fulfillment; reliability; privacy; responsiveness and contact. Analytical techniques to test hypotheses using two-sided test and Importance Performance Analysys to compare user ratings against actual perceptions and expectations. In this study researchers used questionnaires and interviews to internet banking users. The results of data collection processed by using SPSS program version 22. The results prove that there is a differenceÂ  between the actual perception and the ideal expectations of users in each dimension of quality internet banking services that is efficiency; fulfillment; reliability; privacy; responsiveness and contact. The four dimensions found in quadrant I that need to be improved by management are: efficiency (E1); efficiency (E4); fulfillment (F5); and reliability (R9); and four dimensions are in quadrant II that need to be maintained ie reliability (R8 ); Privacy (P13); responsiveness (RP14); responsiveness (RP15) and contact (C17). Bank management can use the results of research as a strategy to improve or maintain the quality of internet banking services.